EFFECT SECRETION AND REMNANTS ROOT SUMMER PLANTS IN GERMINATION AND GROWTH OF WHEAT BREAD PLANTS Triticum aestivum L. - Dawood, Wisam Malik; Al-Khalidi, Raghda Safaa Al-ddin (Diyala Agricultural Sciences Journal, 2017)
Two Experiment was carried out in Biology department/College of Education for pure Science–University of Diyala, during agricultural season 2014–2015; To study the effect of allelopathy of some summer plants; The first experiment was laboratory experiment was designed in Completely Randomized Design (CRD), with three replicates to investigate the effects of roots extracts of summer plants (maize, sorghum, sunflower and cotton) in percentage of germination and some characteristic of seedling growth of wheat seeds. Second experiment was in pots to study the effects of roots residues of maize, sorghum, sunflower and cotton on growth, germination and yield of wheat which was planted after them, according to the Randomized Complete Block Design (R.C.B.D) with four replicates. Result showed a significant decrease in seed germination of wheat reached to (33.333, 86.667, 73.333 and 26.667%) respectively, as compared with control treatment 93.33%. as well as radical and dry matter at transaction with warm water abstracts to roots of the summer plants mentioned with concentration 100%. Also, result of pots experiment showed a significant decrease in seed germination of wheat. While, it gave significant increase in the percent of fertile branches and plant height which was planted after sorghum, weight of 100 grain and yield of grain plant in wheat which was planted after sunflower